Web Page Categorization based on Characteristics of Web Page - Taneja, Khushboo (My University, 2012)
An approach to categorize web pages automatically on the basis of characteristics of web pages using neural network based approach by selecting web specific features to categorize web pages into predefined categories with high accuracy
Keywords: Web Page Categorization; Classification